ニホン ナンキョク チイキ カンソクタイ ノ カキ コウドウチュウ ニオケル カイヒョウ ブンプ ジョウホウ ノ テイキョウ システム - 田村, 岳史; タムラ, タケシ; 清水, 大輔; シミズ, ダイスケ; 牛尾, 収輝; ウシオ, シュウキ; 大島, 慶一郎; オオシマ, ケイイチロウ; Tamura, Takeshi; Simizu, Daisuke; Ushio, Shuki; Ohshima, Kay I. (2011)
P(論文) 最新の高分解能のAdvanced Microwave Scanning Radiometer-EOS (AMSR-E) 海氷密接度データを南極地域観測隊に提供するシステムを開発した.このシステムによって,デジタルデータとしての海氷分布情報が1-2日程度の遅れで第51次及び第52次日本南極地域観測隊に送られ,係留系設置作業に関わる現地判断に役立てることができた.さらに,このデータは東京海洋大学「海鷹丸」や海洋研究開発機構「白鳳丸」等の南極海氷域周辺を航行する他の日本の観測船にも提供され,それぞれの船の運航上の参考情報として役立てられた. We developed a system to supply Advanced Microwave Scanning Radiometer-EOS (AMSR-E) sea ice concentration data to the Japanese Antarctic Research Expedition (JARE). Using this system, digital sea ice concentration data were provided to JARE-51 and -52 on the icebreaker Shirase, with a lag time of 1-2 days. The sea ice data were highly useful during the deployment of the moorings. The system was also utilized by other Japanese research vessels in the Southern Ocean, and the sea ice data were helpful for the operation of the vessels. Errata | http://id.nii.ac.jp/1291/00009645/ departmental bulletin paper